Bacteria‐Assisted Activation of Antimicrobial Polypeptides by a Random‐Coil to Helix Transition. (28th July 2017) - Xiong, Menghua; Han, Zhiyuan; Song, Ziyuan; Yu, Jin; Ying, Hanze; Yin, Lichen; Cheng, Jianjun
Abstract: The application of antimicrobial peptides (AMPs) is largely hindered by their non‐specific toxicity against mammalian cells, which is usually associated with helical structure, hydrophobicity, and charge density. A random coil‐to‐helix transition mechanism has now been introduced into the design of AMPs, minimizing the toxicity against mammalian cells while maintaining high antimicrobial activity. By incorporating anionic phosphorylated tyrosine into the cationic polypeptide, the helical structure of AMPs was distorted owing to the side‐chain charge interaction. Together with the decreased charge density, the AMPs exhibited inhibited toxicity against mammalian cells. At the infectious site, the AMPs can be activated by bacterial phosphatase to restore the helical structure, thus contributing to strong membrane disruptive capability and potent antimicrobial activity. This bacteria‐activated system is an effective strategy to enhance the therapeutic selectivity of AMPs.